2016
DOI: 10.1007/s00441-016-2518-3
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of ABCG1 and PPARγ/LXRα signaling in TLR4 mediates inflammatory responses and lipid accumulation in vascular smooth muscle cells

Abstract: Toll-like receptor 4 (TLR4) plays critical roles in vascular inflammation, lipid accumulation and atherosclerosis development. However, the mechanisms underlying these processes are still not well established, especially in vascular smooth muscle cells (VSMCs). ATP-binding cassette transporter G1 (ABCG1) is one of the key genes mediating inflammation and cellular lipid accumulation. The function of TLR4 in regulating the expression of ABCG1 and the underlying molecular mechanisms remain to be elucidated. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…CRP is produced by different cells, including smooth muscle cells, macrophages, lymphocytes and adipocytes, and activates the classical complement pathway [8].Thiazolidinediones insignificantly decreased TNF alfa levels in Type 2 DM patients or had no effect on TNF-α and sCD40L; our data are consistent with the Manning et al's study [12,13]. Recently, Cao X et al suggested that Toll-like receptor 4 (TLR4) played a critical role in vascular inflammation, lipid accumulation, and atherosclerosis development [14]. Activation of TLR4 signaling via oxidized low-density lipoprotein (oxLDL) inhibited expression of peroxisome proliferator-activated receptor gamma (PPARγ), liver X receptor alpha (LXRα) and ABCG1.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…CRP is produced by different cells, including smooth muscle cells, macrophages, lymphocytes and adipocytes, and activates the classical complement pathway [8].Thiazolidinediones insignificantly decreased TNF alfa levels in Type 2 DM patients or had no effect on TNF-α and sCD40L; our data are consistent with the Manning et al's study [12,13]. Recently, Cao X et al suggested that Toll-like receptor 4 (TLR4) played a critical role in vascular inflammation, lipid accumulation, and atherosclerosis development [14]. Activation of TLR4 signaling via oxidized low-density lipoprotein (oxLDL) inhibited expression of peroxisome proliferator-activated receptor gamma (PPARγ), liver X receptor alpha (LXRα) and ABCG1.…”
Section: Discussionsupporting
confidence: 91%
“…PPARγ activation by Rosiglitazone induced LXRα and ABCG1 expression and reduced TLR4 induced inflammation. Cao et al showed that Rosiglitazone treatment inhibited IL-6 and MCP-1 mRNA expression but not that of TNF-α [14]. It has been suggested that the anti-inflammatory effect of PPARγ activators was related to PPARγ-dependent or PPARγ-independent mechanisms [14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toll-like receptor 4 (TLR4), a typical representative of pattern recognition receptors in innate immune responses, which can activate the transcription factors nuclear factor-κB (NF-κB) leading to the production of proinflammatory cytokines [ 49 ]. Toll-like receptor 4 mainly regulates ABCG1 , which is a key gene that mediates inflammation and cellular lipid accumulation [ 50 ]. Toll-like receptor 4 induces inflammation and lipid accumulation in VSMCs by downregulating ABCG1 expression through the Peroxisome proliferator activated receptor gamma (PPAR γ)/liver X receptor alpha (LXRα) signaling pathway [ 51 ].…”
Section: Atherosclerosis Related Inflammatory Signaling Pathwaysmentioning
confidence: 99%
“…In recent years, there has been an increasing body of evidence pointing to the possibility that metals can alter epigenetic factors and cardiovascular risk [4]. Among the metal-DMR genes, we identified three genes encoding atherosclerosis-effector proteins (IRF1, PF4 and TLR4), which are either involved in unbalanced lipid metabolism or chronic inflammation of the arterial wall [66][67][68]. Others genes, including SMAD3, HLA-C, GNAS or SDK1, have been previously reported as differentially methylated in CVDs [11,13,34,35], and some of these had a strong and medium-strong score of relationship with atherosclerosis in our ANN analysis.…”
Section: Discussionmentioning
confidence: 99%